The mediating role of positive perceptions on coping strategies and psychological well-being among mothers of children with intellectual disabilities. Issue 6 (28th November 2020) - Gupta, Simmi; Kumar, Aneesh
Abstract : Purpose: Research on caregiving has been considering the positive effects experienced by the mothers of children with disabilities. This paper aims to examine whether positive perceptions mediate the relationships between coping strategies used and psychological well-being among mothers of children with intellectual disabilities. Design/methodology/approach: The study opted for a quantitative approach that includes a correlation research design to examine the relationships between the variables of coping, positive perceptions and well-being among mothers of children with intellectual disabilities attending special schools in the metropolitan city Bengaluru, India. The four-factor structure of Brief COPE examined were active avoidance coping, problem-focussed coping, positive coping and religious-denial coping. "Positive perceptions" refer to the positive contributions for the mother from the experiences of raising a child with intellectual disability. Mediation analysis explored the relationship between the variables. Findings: Problem-focussed coping was the most commonly reported coping factor and was associated with higher levels of well-being. Active-avoidance coping was the least commonly reported coping strategy. Positive perceptions partially mediated the relationship between the four coping factors and maternal well-being. These findings indicate that positive maternal perceptions have important implications for the employment of effective coping strategies that are associated with enhancement of psychological well-being. Originality/value: The focus on positive perceptions would help in understanding the use of coping strategies and planning of support services or interventions. The positive mental health of mothers paves the way for positive developments in the child's physical and psychological health.